Comparison between Percutaneous Needle Release and Local Corticosteroid Injection for the Treatment of Tennis Elbow - Lekkreusuwan, MD, Kreangsak; Toraudom, MD, Yingyong (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: The goal of treatment of tennis elbow is to treat tendinosis. Percutaneous needle release is one of the treatment options but does not have comparative outcomes with standard treatments. To compare the clinical outcomes between percutaneous needle release and local corticosteroid injection in tennis elbow disease. Methods: A prospective randomized controlled study was conducted. Forty-nine tennis elbow patients were divided into two groups by randomization. Twenty-four patients were assigned to the corticosteroid injection group and 25 patients were assigned to the percutaneous needle release group. Both groups were assessed for visual analog scale (VAS), grip strength, and infection before treatment and 2 weeks, 1, 2, 3, and 6 months after the procedures. Results: All demographic data, baseline VAS, and grip strength were not statistically different between groups. The difference of VAS compared to baseline at 2 weeks, 1, 2, 3, and 6 months were 5.86, 6.14, 5.57, 5.09, and 4.85 for the corticosteroid group and 2.68, 3.93, 4.74, 4.38, and 4.35 for the percutaneous needle release group, respectively. The difference of grip strength compared to baseline at 2 weeks, 1, 2, 3, and 6 months were 8.73, 10.42, 10.83, 9.55, and 8.55 for the corticosteroid group and 3.43, 4.65, 7.80, 6.88, and 7.06 for the percutaneous needle release group, respectively. The improvement of VAS and grip strength in the corticosteroid group was superior to the percutaneous needle release group, but there was statistical significance only at 2 weeks and 1 month follow ups (P = <0.001, <0.001, 0.001, 0.005, respectively). No case of infection was detected during the follow up period. Conclusion: A corticosteroid injection improved pain and grip strength in tennis elbow disease more than percutaneous needle release, but was statistically significant only at 2 weeks and 1 month after treatments.